Reactive carbonyl compounds impair wound healing by vimentin collapse and loss of the primary cilium. (October 2017) - Rodríguez-Ribera, Lara; Slattery, Craig; Mc Morrow, Tara; Marcos, Ricard; Pastor, Susana
Abstract: In renal pathologies tubulo-interstitial fibrosis results from an aberrant wound-healing ability where the normal epithelial tissue is substituted for scar tissue caused by accumulation of extracellular matrix proteins (ECM). During the wound-healing process, epithelial cells may undergo epithelial-mesenchymal transition (EMT) acquiring a mesenchymal-like phenotype that allows cells to migrate and re-epithelialize the wound site. It has been reported that chronic inflammation and uremic milieu are involved in wound-healing and enhanced kidney damage in chronic kidney disease (CKD) patients. In this study we evaluated reactive carbonyl compounds (RCC) effects on renal wound healing. The compounds resulting from carbonyl stress evaluated in this study were glyoxal (GO), methylglyoxal (MGO), malondialdehyde (MDA) and 4-hydroxy-hexenal (HHE). Wound repair ability was evaluated by the wound healing assay using HK-2 cells. EMT was evaluated by morphological, protein and transcriptional changes using microscopy, western blot, zymography and RT-qPCR. Changes in the vimentin network and primary cilia were assessed by immunofluorescence. Our data demonstrated that MDA and GO delay wound closure mediated by vimentin disruption, which caused collagen I mRNA decrease, and deciliation. In contrast, HHE treatment (and MGO to a minor degree) induced morphological changes and increased mesenchymal marker expression and gelatinase activity in HK-2 cells. In this study, we have demonstrated for the first time that exposure to RCC differentially affects wound healing in proximal tubular epithelia. A better comprehension of effects of uremic toxins on wound healing and fibrosis and migration is necessary to seek mechanisms to slow down renal fibrosis. Highlights: Effects of reactive carbonyl compound on wound healing process were determined. Glyoxal (GO), methyl-glyoxal (MGO), malondialdehyde (MDA) and 4-hydroxy-hexenal (HHE) were evaluated. MDA and GO delay wound closure mediated vimentin disruption. HHE induced morphological changes and increased mesenchymal markers expression.